Determination of Optimal Fluoroscopic Angulations for Left Main Coronary Artery Ostial Interventions: 3-Dimensional Computed Tomography Validation - Yuhe Sheng; Jie Yu; Quanmin Jing; Yaling Han; Yi Li; Kai Xu; Miaohan Qiu; Yingdong Wang; Gary S. Mintz; Bin Wang (Journal of Interventional Cardiology)
Background. Current recommendations for the best views for the left main coronary artery (LMCA) ostium intervention are empirical. Objectives. To determine the optimal projection to visualize the LMCA ostium using only fluoroscopy. Methods. The optimal projection to visualize the LMCA ostium was determined using fluoroscopic images of superimposing the lowest points of the distal ends of two J tipped wires in the noncoronary cusp (NCC) and right coronary cusp (RCC). This was validated independently using 3-dimensional computed tomography (3D-CT) reconstruction. Results. Satisfactory images of the overlapping wires in NCC and RCC could be obtained in 90% (45/50). Between the fluoroscopic and the 3D-CT reconstruction approaches, the mean difference for NCC and RCC overlapping at horizontal axes is -1.8 with a 95% limit of agreement between −3.94 and 0.34 p=0.10 and at vertical axes −1.6 with a 95% limit of agreement between −3.46 and 0.26 p=0.09; and the mean difference for the optimal projection to visualize the LMCA ostium at horizontal axes is −3.22 with a 95% limit of agreement between -7.26 and 0.81 p=0.11 and at vertical axes −2.31 with a 95% limit of agreement between −5.83 and 1.21 p=0.09. The 3D angulation deviation for the optimal projection to visualize the LMCA ostium was 8.5° ± 4.7° when the LMCA ostium faced the NCC-RCC commissure (n = 32) and 22.3° ± 16.0° p=0.009 when it did not (n = 13). Conclusions. The optimal projection for LMCA ostial intervention can be determined using fluoroscopic images of superimposing wires in the NCC and RCC when the LMCA ostium faces the NCC-RCC commissure, as was the case in 71% of the patients studied.